When Systems Clash: The Case for a Single Regulatory Body for Licensing - Philip Alan Kolvin (Entertainment and Sports Law Journal)
This article examines what happens when the same subject matter is or could be controlled by different licensing regimes. It suggests that the system of control of licensed premises would be improved by appointing a single regulatory body for licensing.